The endodermal passage cell – just another brick in the wall?. Issue 4 (14th March 2021) - Holbein, Julia; Shen, Defeng; Andersen, Tonni Grube
Summary: The endodermis surrounds and protects the vasculature partly by depositing hydrophobic suberin in the cell walls. Yet, some cells remain unsuberised. These historically termed 'passage cells' are assumed to provide a low‐resistance pathway to the xylem. Only recently have we started to gain molecular insights into these cells, which allow us to probe how roots coordinate communication with the environment across barriers with single‐cell precision. Increased understanding of root physiology at a high‐resolution is intriguing, as it is likely to provide us with new tools to improve overall plant health. With this in mind, we here provide a brief overview of passage cells, their presence across plant species, as well as a molecular update and future directions for passage cell‐related research.